The Effect of Financial Literacy and Income on Personal Financial Management Behavior of Millennials in Yogyakarta, Indonesia - Dyah Ari Susanti (Universitas Sarjanawiyata Tamansiswa, 2021)
Millennials are individuals who were born between 1980 and 2000. Millennials currently account for one-third of the total population, so they play an important role in contributing to the economy. Unfortunately, today's millennial generation is faced with negative impact platforms such as a high lifestyle, consumptive nature, and also the use of credit cards. The millennial generation needs knowledge of financial decisions to avoid current and future financial problems. Considering the You Only Live Once lifestyle or so-called â€œYOLOâ€ millennials lead to consumptive choices at a young age, this needs to be controlled. On the other hand, the world faces the Covid-19 pandemic, which has greatly impacted the country's economy. In this study, the influence of financial literacy and income factors on the personal financial management behavior of the millennial generation in Yogyakarta. The study was taken from respondents in one of a private university located in Yogyakarta. The model obtained is Y=43,844+0,92X1+0,28X2, where Y is Financial management behavior, X1 is Financial Literacy, and X2 is Income.